Fueling change: Impact of mass media on clean cooking fuel adoption in rural India - Cledwyn Fernandez; Havishaye Puri (Asian Development Bank Institute (ADBI), 2024)
Our paper analyzes the causal impact of access to mass media on the adoption of clean cooking fuel in rural India. Using the 78th round of the National Sample Survey of India, we find that overall access to mass media increases the probability of using clean cooking fuel by 32 percentage points and reduces the probability of using dirty cooking fuel by 35 percentage points. To test for causality, we use an instrumental variable technique with two instruments. Our first instrument is the States/UTs-wise circulation of publications per capita, and our second instrument is the States/UTs-wise number of push SMSs sent per capita through the Government of India's Mobile Seva platform. Given the recent drive by the government to disseminate policy-related information digitally, we isolate the impact of digital mass media on the adoption of clean cooking fuel and find that digital mass media positively and significantly impacts adoption of clean cooking fuel. However, this impact is considerably weaker than the unconditional impact of mass media access. This suggests that the adoption of clean cooking fuel is still mostly driven by traditional mass media channels rather than digital ones.
Keywords: C36; I18; O13; Q50; 330; mass media; clean fuel; digital; rural; India